Penerapan Model Digital Marketing Aida Dalam Pengembangan Media Sosial (Studi Kasus Umkm Desa Baturiti) - Sudana Putra; Ngurah Gede Dwi Mahadipta; Muhammad Febrian Rachmadhan Amri; Putu Yogi Agustia Pratama; Zulfikar Sa’ban (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2025)
This research seeks to investigate how well the AIDA (Attention, Interest, Desire, Action) marketing framework performs in guiding social media strategies to boost brand visibility and revenue for Dapur Yura, a small to medium-sized enterprise (SME) located in Baturiti Village. The study utilized an experimental methodology, gathering both qualitative and quantitative data through observation, personal interviews, analysis of digital content insights, and practical testing. The findings reveal that applying a social media marketing tactic based on the AIDA framework significantly raised Dapur Yura's Return on Investment (ROI) from 50% to 118%. Additionally, the SME's social media metrics exhibited a remarkable enhancement in impressions, account reach, and user engagement when juxtaposed with prior to the advertisement rollout and also when compared to other similar SMEs that rely solely on organic content management. This study concludes that the AIDA framework serves as an effective tool for optimizing social media strategies for SMEs, resulting in improved brand recognition and increased sales.